A New Type of Stereoselectivity in Baeyer–Villiger Reactions: Access to E‐ and Z‐Olefins. Issue 1 (7th January 2013) - Zhang, Zhi‐Gang; Roiban, Gheorghe‐Doru; Acevedo, Juan Pablo; Polyak, Iakov; Reetz, Manfred T.
Abstract A new concept for accessing configurationally defined trisubstituted olefins has been developed. Starting from a common ketone precursor of the type 4‐ethylidenecyclohexanone, Baeyer–Villiger monooxygenases are employed as catalysts in diastereoselective Baeyer–Villiger reactions leading to the corresponding E‐ or Z‐configurated lactones. Wild‐type cyclohexanone monooxygenase (CHMO) as catalyst delivers the E‐isomers and a directed evolution mutant the opposite Z‐isomers. Subsequent transition metal‐catalyzed chemical transformations of a key product containing a vinyl bromide moiety provide a variety of different trisubstituted E‐ or Z‐olefins. A model based on QM/MM sheds light on the origin of this unusual type of diastereoselectivity. In contrast to this biocatalytic approach, traditional Baeyer–Villiger reagents such as m‐CPBA fail to show any selectivity, 1:1 mixtures of E‐ and Z‐olefins being formed.